2005
DOI: 10.1007/s10571-004-1380-0
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Targeting of ICAM-1 Signaling in Brain Endothelial Cells: Potential for Treating Neuroinflammation

Abstract: (1) The vasculature of the blood-brain barrier allows only comparatively few leukocytes to enter and survey the healthy central nervous system (CNS). However, during pathological CNS inflammation, the number of leukocytes adhering to and penetrating the CNS vasculature increases strongly. (2) Endothelial adhesion molecules do not only mediate firm adhesion of leukocyte to vascular beds but also trigger signaling cascades within the endothelial cell, which play a crucial role in modulating subsequent leukocyte … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
63
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 107 publications
5
63
0
Order By: Relevance
“…Several lines of evidence support that ICAM1-mediated direct cell contact has a major impact on a wide range of biological responses including cell differentiation (Gortz et al 2004, Long et al 1995, Olsen et al 1988, Saho et al 2003, Tanaka et al 1995. It has been shown that ICAM1 plays an important role in direct cell-to-cell contact-mediated signals via mitogen-activated protein kinase (MAPK) pathway including p38, extracellular signal-regulated kinase (ERK) 1/2 and c-Jun N-terminal kinase (JNK) 1/2/3 (Cernuda-Morollon and Ridley 2006, Turowski et al 2005), which could subsequently stimulate osteoblast differentiation of stem/progenitor cells. Fu et al (2009) further suggested that ICAM1 and p38 MAPK also significantly influence the migration of stem cells to their target sites, such as PDL tissue and alveolar bone.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence support that ICAM1-mediated direct cell contact has a major impact on a wide range of biological responses including cell differentiation (Gortz et al 2004, Long et al 1995, Olsen et al 1988, Saho et al 2003, Tanaka et al 1995. It has been shown that ICAM1 plays an important role in direct cell-to-cell contact-mediated signals via mitogen-activated protein kinase (MAPK) pathway including p38, extracellular signal-regulated kinase (ERK) 1/2 and c-Jun N-terminal kinase (JNK) 1/2/3 (Cernuda-Morollon and Ridley 2006, Turowski et al 2005), which could subsequently stimulate osteoblast differentiation of stem/progenitor cells. Fu et al (2009) further suggested that ICAM1 and p38 MAPK also significantly influence the migration of stem cells to their target sites, such as PDL tissue and alveolar bone.…”
Section: Discussionmentioning
confidence: 99%
“…Aging-associated BBB modifications are due, at least in part, to a significant age-dependent reduction in the number of lamininpositive [20] and collagen-type-IV-containing vessels [33], and reduced capillary density [34]. In addition, in several pathological conditions of the CNS, associated inflammation alters BBB morphology and function, inducing adherence of leukocytes to the vasculature, and penetration into the CNS [11,35,36].…”
Section: Aged-induced Changes In Neutrophil Densitymentioning
confidence: 99%
“…The endothelial intercellular adhesion molecule-1 (ICAM-1, CD54), an immunoglobulin surface receptor, has been shown to induce changes in the endothelial cytoskeleton, transcription and interendothelial junctions, factors which may modulate endothelial disposition to infiltrating leukocytes (Turowski et al, 2005). Using CIP, Huber et al (2006) showed an increase in ICAM mRNA and protein expression at the BBB.…”
Section: Introductionmentioning
confidence: 99%